2006
DOI: 10.1038/sj.ijo.0803282
|View full text |Cite
|
Sign up to set email alerts
|

Effects of obesity phenotype on fat metabolism in obese men during endurance exercise

Abstract: Objective: The effects of obesity phenotype on fat metabolism during endurance exercise are unclear. This study aimed to investigate in obese men whether body fat distribution would influence plasma fat availability and oxidation during endurance exercise. Design: Fourteen sedentary men (body mass index (BMI)425 kg/m 2 ) were divided into two groups by visceral fat (VF) area: VF obese (VF-Ob) (n ¼ 7, age; 52.072.5 (s.e.) years) and abdominal subcutaneous fat obese (SF-Ob) (n ¼ 7, age; 57.372.8 (s.e.) years). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
(54 reference statements)
2
8
2
Order By: Relevance
“…In the present study, the men and women differed in visceral fat and subcutaneous fat areas and in waist-to-hip ratio; however, these variables did not correlate with fat oxidation adjusted for FFM and average RER during aerobic exercise (data not shown). In this regard, our findings are therefore consistent with the results of previous studies [40][41][42][43].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…In the present study, the men and women differed in visceral fat and subcutaneous fat areas and in waist-to-hip ratio; however, these variables did not correlate with fat oxidation adjusted for FFM and average RER during aerobic exercise (data not shown). In this regard, our findings are therefore consistent with the results of previous studies [40][41][42][43].…”
Section: Discussionsupporting
confidence: 95%
“…Previous studies have found that abdominal fat distribution does not influence substrate oxidation during exercise in subjects of the same sex [40][41][42][43]. In the present study, the men and women differed in visceral fat and subcutaneous fat areas and in waist-to-hip ratio; however, these variables did not correlate with fat oxidation adjusted for FFM and average RER during aerobic exercise (data not shown).…”
Section: Discussioncontrasting
confidence: 80%
“…On the other hand, IF tissue has lower antilipolytic responses to insulin compared to SF tissue [33], which gradually decreases during prolonged exercise. A previous report [16] indicated higher lipid concentrations in HIF 245 obesity than MIF obesity in men. However, whole-body fat oxidation did not differ between HIF and MIF obesity phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…It has 45 been suggested that potential influencing factors include physiological, environmental and genetic attributes. Obesity phenotype is a possible factor influencing IF responses to regular aerobic exercise because of increased fat availability during a single bout of prolonged aerobic exercise in IF type obesity [16]. One study examined whether obesity phenotype would affect the IF response to a weight-loss intervention in 50…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the blood levels of several hormones such as catecholamines, glucagon, growth hormone and cortisol are increased by acute exercise 6) . Moreover, several studies reported on acute exercise and lipid utilization, and related hormones in obese subjects [7][8][9] . Therefore, we hypothesize that a combination of acute exercise and the factors that affect the secretion of some of these hormones may be effective for increasing fat catabolism.…”
Section: Introductionmentioning
confidence: 99%